Consumer price adjustment under the microscope: Germany in a period of low inflation - Johannes Hoffmann; Jeong-Ryeol Kurz-Kim (European Central Bank (ECB), 2006)
We analyse the adjustment of retail and services prices in a period of low inflation, using a set of individual price data from the German Consumer Price Index that covers the years 1998 to 2003. We strong find evidence of time- and statedependent price adjustment. Most importantly, the differences in “unconditional” sectoral price flexibility are found to be linked to input price volatility.
Keywords: E31; D43; L11; 330; consumer price index; Germany; price flexibility; price rigidity; Verbraucherpreisindex; Preisrigidität; Preis; Inflation; Deutschland; Flexibilität